1986
DOI: 10.3354/meps032139
|View full text |Cite
|
Sign up to set email alerts
|

Diel patterns of cell division in marine Synechococcus spp. (Cyanobacteria): use of the frequency of dividing cells technique to measure growth rate

Abstract: Natural populations of the planktonic cyanobacteria Synechococcus spp. exhibit a diel pattern in the frequency of dividing cells (FDC). Based on this observation, we tested the applicability of the FDC technique for estimating growth rate of a population grown on a IighWdark cycle. In laboratory experiments, the phycoerythrin-containing strains WH7803, WH8012, WH8107, and WH8108 were grown under various light and temperature conditions and the duration of division, td, a parameter necessary for the calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
5

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 24 publications
12
51
5
Order By: Relevance
“…Similar diel patterns have been reported for FDC of heterotrophic bacteria by Kuipers et al (2000). Also, FDC values of picophytoplankton were higher in the early evening in natural environments (Campbell & Carpenter 1986). These similarities indicated that the pattern of higher division rate during night might be prevalent in marine microorganisms.…”
Section: Diel Variations Of Fdc Of Aap Bacteria Versus Total Bacteriasupporting
confidence: 66%
“…Similar diel patterns have been reported for FDC of heterotrophic bacteria by Kuipers et al (2000). Also, FDC values of picophytoplankton were higher in the early evening in natural environments (Campbell & Carpenter 1986). These similarities indicated that the pattern of higher division rate during night might be prevalent in marine microorganisms.…”
Section: Diel Variations Of Fdc Of Aap Bacteria Versus Total Bacteriasupporting
confidence: 66%
“…The highest division rates of Synechococcus were realized in early evening, i.e. 12 to 15 h after dawn (Campbell & Carpenter 1986a), whereas Prochlorococcus started cell division after sunset . Therefore, dawn-to-dusk incubations underestimate the 'true' daily growth rate, especially for Prochlorococcus.…”
Section: Discussionmentioning
confidence: 98%
“…The growth rate of Synechococcus has been studied quite intensively (Landry et al 1984, Campbell & Carpenter 1986a, b, Iturriaga & Mitchell 1986, Iturriaga & Marra 1988, Burkill et al 1993). In contrast, there are only a few recent reports of the growth rates of Prochlorococcus (Goericke & Welschmeyer 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Cells undergoing division and having a complete cross wall between daughter cells were also counted. The frequency of cells in division (FDC) was determined by dividing the cells undergoing division by the total number of cells counted (Campbell and Carpenter 1986). To obtain reliable estimates of abundance, at least 1000 virus particles, 800 bacteria, and 200 Synechococcus spp.…”
Section: Virus Bacteria and Synechococcus Spp Abundance Countsmentioning
confidence: 99%